Panel recovery after 22 years: how we reactivated a 45 year cohort study in Canada. (1st January 2021) - Robson, Karen; Anisef, Paul; Northrup, David; Grearson, Adam
Abstract : In this paper we describe the process we used to reactivate a cohort study that began in 1973 but had not been contacted since 1995. In 2018, we began efforts to trace cohort members who had been involved in the last wave of the study. While we had old contact information, we also employed internet search strategies to try to find individuals. We discuss our strategy and the limits that we have as Canadians working in an extremely limited funding landscape and a data infrastructure that does not allow access to government data sources, like those described by researchers of other similar longitudinal studies spanning decades in the UK and the US. Despite our considerable attrition, we performed some analyses that demonstrates our remaining cohort is not that dissimilar from either the original cohort or in terms of general characteristics of Ontarians in their mid-60s.